Методы измерения фазового сдвига с промежуточным преобразованием напряжение-частота - Чинков, В. Н.; Мунтян, Ю. А. (НТУ "ХПИ", 2008)
В статті розглянуті методи вимірювання фазового зсуву з проміжним перетворенням напруга-частота. Проаналізовано переваги й недоліки методів. Проведено оцінку похибки, обумовленої неточністю формування часових інтервалів.

In article methods of measurement of phase shift with preliminary transformation a voltage-frequency are considered. Their merits and demerits are analyzed. The estimation of the error caused by discrepancy of formation of time intervals is made.
Keywords: импульс частоты; дифференцирование; фазовый сдвиг; погрешности; коэффициенты